Community and City Government Participation in Coastal Coastal Area Conservation: a study in Pariaman City. - ithvi marhamah (LPPM Universitas PGRI Sumatera Barat, 2020)
Irregularities in spatial use that are not in accordance with regional planning resulting in reduced protected and buffer zone space in Pariaman City. The research objective was to analyze the causes of the deviation in spatial use from the point of view of the sustainability of the coastal area in Pariaman City. The research method is a combination of qualitative research methods with quantitative research methods using a spatial approach using geographic information systems (GIS). The results show that the harmonization analysis between Law 26 of 2007 article 5 and Law 1 of 2014 article 9 and RTRW are appropriate: Coastal areas are used as protected and buffer areas, but the use of existing land is not in accordance with the harmonization analysis of the two laws and regulations. By the existence of a built-up area in an area that should be a buffer zone. The participation of the community and city government in the management of the coastal area causes this deviation: Lack of knowledge of residents about the zoning of customary rights over are two contributing factors. The city government which prioritizes the economic development of coastal areas with tourism development threatens the ecology and coastal resources Keyword: Environmental Management, Conservation, Coasta areas, Community participation, Zoning